Exploration of economic and environmental impacts of crop diversification in the northwestern IGP of India - Singh, L. K.; Bijarniya, Deepak; Prajapat, Kailash; Jat, H. S.; Choudhary, Madhu; Sharma, P. C.; Kalvania, K. C.; Yadav, R. K.; Jat, M. L.; Krupnik, Timothy J.; Gathala, Mahesh K. (TAFSSA, 2024)
The energy-intensive rice-wheat system in the northwestern Indo-Gangetic Plain (NWIGP) significantly increases production costs and greenhouse gas (GHG) emissions, driven by chemical fertilizers, fossil fuels for intensive tillage, irrigation, and high labor use. A particularly harmful practice is residue burning, commonly used to clear fields after harvest, releasing large amounts of carbon dioxide and particulate matter, worsening air pollution, and posing health risks to local communities. To address these challenges, on-station research was initiated in collaboration with the ICAR-Central Soil Salinity Research Institute (CSSRI) and the Transforming Agrifood Systems in South Asia (TAFSSA) initiative under CIMMYT. The research focuses on reducing cultivation costs, improving farm profitability, decreasing energy use, and lowering GHG emissions through diversified cropping systems.